Microbial γ-polyglutamic acid (γ-PGA) incorporation into muffins: Impact on physico-chemical, functional, and textural properties - Manika, Verma; Devi, Palanisamy Bruntha; Reddy, G. Bhanuprakash; Kavitake, Digambar; Shetty, Prathapkumar Halady (Frontiers in Food Science and Technology, 2025)
This study investigated the effects of gamma‐(γ)‐polyglutamic acid (γ‐PGA) on the physical, structural, and sensory properties of muffins. γ‐PGA polymer, extracted from Bacillus valezensis M‐E6, was incorporated into muffin batter at concentrations ranging from 0.2% to 1%. The volume index of muffins was increased to 104 with γ‐PGA (0.6%) compared to the control muffins (without γ‐PGA, 95.3). Textural profile analysis revealed the best texture for muffins containing 0.6% γ‐PGA, characterized by the lowest hardness (1508 g), which was half that of muffins without γ‐PGA, along with improved cohesion and springiness. The viscosity of control batter was 12648 mPa·s, whereas for γ‐PGA batter, it was 14845 mPa·s. Also, a decrease in lightness (L*) and an increase in redness (a*) were observed in muffins with γ‐PGA. γ‐PGA muffins received higher overall acceptability scores than the control in the sensory evaluation. The antioxidant activity of the muffin increased from 6% to 41% when incorporated with γ‐PGA, which makes it a functional muffin. Incorporating γ‐PGA improved the physical, textural, and sensorial properties of muffins, making it a promising natural ingredient for enhancing the quality and shelf life of baked products. These results suggest that γ‐PGA not only improves the texture and quality of muffins but also benefits moisture retention and shelf life, aligning with consumer preferences for natural and sustainable food ingredients.